Suppression of wheal and flare in histamine test by the main H1 antihistamines commercialized in Brazil - Helena Maciel-Guerra; Mariana Álvares Penha; Marília Formentini Scotton Jorge; Ricardo da Silva Libório; Ana Cláudia Nazareno dos Anjos Carrijo; Maria Rita Parise-Fortes; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Several dermatoses are mediated by histamine, such as urticaria, angioedema, and papular urticaria. There are no Brazilian studies comparing the potency of antihistamines. Objectives: To evaluate the tolerability and efficacy of the main commercial brand and generic H1 antihistamines, regarding the suppression of the wheal and flare to the histamine test. Methods: A quasi-experimental, open study with 10 healthy adults submitted to the histamine test on the ventral aspect of the forearms. After 20 minutes, wheal and flares were measured. The tests were performed after two hours of intake of dexchlorpheniramine, hydroxyzine, levocetirizine, fexofenadine, cetirizine, loratadine, ebastine, desloratadine, epinastine and rupatadine, as well as generics of loratadine, cetirizine and fexofenadine. Results: All antihistamines presented a reduction in the wheal compared to the control (p <0.02), as well as in the flare, except for rupatadine (p = 0.70). In the internal comparison, cetirizine, fexofenadine, epinastine, levocetirizine, dexchlorpheniramine and hydroxyzine were the most potent, with no difference between them (p > 0.1). As for halo, cetirizine, epinastine, hydroxyzine and fexofenadine were the most potent, with no difference between them (p > 0.1). The most common adverse effect was drowsiness, which was more prevalent among first-generation drugs (p < 0.01). Generic loratadine, fexofenadine and cetirizine halos were higher than their controls (p <0.03).. Study limitations: A single-center study evaluating only aspects related to histamine. Conclusions: Brazilian commercial antihistamines presented different profiles of inhibition of wheal and flares in the histamine test, as well as adverse effects. Generic loratadine, fexofenadine and cetirizine presented larger flares than brand drugs.